Basis Weight Gain Tuning Using Different Types of Conventional Controllers - Chandani Sharma; Anamika Jain (Institute of Advanced Engineering and Science, 2016)
Paper making is a vast, multidisciplinary technology that has expanded tremendously in recent years approaching to reach 20 million tons by 2020. As per demand implementation of necessary tools to optimize papermaking process and to increase the control precision, the precondition for stable operation and quality production is necessary. In the present work, an effort has been made to analyse gain tuning of Basis Weight output relative to the changing values of basis weight valve opening with step and variable input. The effects of the three constants KP, KD and KI for different types of conventional controllers as P, PD and PID controller are examined by adding a disturbance to the control system. The effects of various scaling gains are studied on the output of the system and are tuned to get the optimum output both for the step input as well as the varying input. Simulation results show that P, PD and PID controllers provide automatic tuning to preserve good performance for various operating conditions. An analysis of practical performance indices is presented by comparing results of three different conventional controllers. The system developed can be used to serve as platform for Control engineering techniques used in industries.